critical study in the subject-matter of the contract and the obligation - Jumaa, Ali; Hasan, Jaleel (Journal of Legal Sciences, 2022)
The topic of subject-matter is one of the thorny issues in civil law, as this topic despite its antiquity still represents a fertile ground for research , There is a dispute about the determination of the legal object in which subject-matter is element in it ,Where the legislation differs on this issue , Some legislation states that the subject matter is an element of a contract, and Some of them states that the subject matter is an element of an obligation, and Some of them states that the subject matter is an element of a contract and an obligation , This dispute has moved to jurisprudence, There were several directions in it , The research ended with us saying that the subject matter is an element of a contract.